Bacterial profile and antimicrobial susceptibility pattern of uropathogens among suspected patients attending Bule Hora University Teaching Hospital, southern Ethiopia - Edin, Alo; Tilahun, Dagnamyelew; Jara, Berhanu Adula; Ayele, Angefa (Frontiers in Bacteriology, 2025)
BackgroundAntimicrobial resistance can vary significantly across different regions, making it crucial to understand the distribution of urinary pathogens and their susceptibility to antibiotics in specific settings. This knowledge is essential for guiding effective empirical treatment approaches. Additionally, antimicrobial resistance is an ongoing process that requires routine surveillance and monitoring studies to stay ahead of emerging resistance patterns. In Ethiopia, including southern Ethiopia, there is a lack of recent data regarding the magnitude of the problem of antimicrobial resistance in urinary tract infections (UTIs). Due to limited microbiology laboratory capabilities, routine culture and antibiotic susceptibility testing are not performed in the region. Consequently, the treatment of UTIs in Ethiopia relies on an empirical basis, with physicians prescribing different drugs without the guidance of culture and antibiotic susceptibility tests. This practice can potentially contribute to the overuse of antibiotics and the development of resistant microbial species. To address this knowledge gap and promote the rational use of existing antimicrobials, it is essential to have up-to-date information on the prevalence of uropathogens causing UTIs and their antimicrobial susceptibility patterns. This study aims to determine the most prevalent uropathogens causing UTIs and their susceptibility to antimicrobial agents among individuals suspected of having UTIs in the study area. By conducting this study, we aim to provide valuable insights into the current situation of antimicrobial resistance in UTIs in southern Ethiopia. This information will help guide clinicians in selecting appropriate antibiotics for empirical treatment and contribute to the overall efforts in combating antimicrobial resistance.Methods and materialsA cross-sectional study was carried out from April to September 2022 at Bule Hora University Teaching Hospital. The study included a total of 279 suspected patients who visited the outpatient department. Sociodemographic data and associated factors were assessed using a pretested questionnaire. Clean catch midstream specimens were collected following standard microbiological procedures. The identification of gram-negative organisms was done using TSI, oxidase, H2S production, gas production, motility, indole production, urease production, citrate utilization, and lysine decarboxylation and deamination. Antibiotic susceptibility testing of the isolates was conducted using the Kirby–Bauer disc diffusion method. Data analysis was performed using SPSS version 25, and descriptive statistics were used to summarize the findings. The results were presented in words and tables. Binary logistic regression was used to determine the statistical association between predictors and outcome variables.ResultsA total of 279 individuals participated in the study. The overall prevalence of gram-negative uropathogens was 11.8%. The predominant bacteria isolated was Escherichia coli (57.7%) followed by Klebsiella species (n = 9, 27.3%) and Proteus species (n = 3, 9.1%).ConclusionBacterial uropathogens, especially resistant strains of E. coli, pose a significant threat. Amoxicillin–clavulanic acid, trimethoprim–sulfamethoxazole, and ciprofloxacin were found to be ineffective against these strains. Regular surveillance of uropathogenic bacteria’s sensitivity to antibiotics can help clinicians make better treatment choices. More research is needed on both gram-positive and gram-negative bacteria, focusing on the molecular characterization of resistant genes.